Communication dynamics: Fintech’s role in promoting sustainable cashless transactions - Weidong Huo; Wang Xiohui; Muhammad Zulfiqar; Ahmed Chand; Muhammad Rizwan Ullah (Humanities & Social Sciences Communications, 2024)
Abstract The integration of Fintech is revolutionizing global financial engagement, moving away from traditional payment systems. This study, thus, explores the interaction between communication dynamics, Fintech use, intentions, cashless transactions adoption, financial literacy, personal innovativeness, and socioeconomic development in Pakistan. The study employs a dual methodology, encompassing “PLS-SEM and Probit Model alongside Propensity Score Matching technique.” The survey targeted small business owners and individuals involved in informal sectors, encompassing roles such as fruit and vegetable vendors, small shop owners, taxi drivers, and auto rickshaw operators. A total of 394 responses were analyzed. The findings highlight the facilitating role of individuals’ intentions to use cashless transactions, acting as a mediator through which Fintech use fosters actual behavior. Moreover, the study finds financial literacy and personal innovativeness as critical moderating factors. Adopting cashless transactions emerges as a pathway to enhanced financial inclusion, particularly impactful for small business owners. The achieved financial inclusion has the potential for profound financial inclusion implications, as evidenced by its positive effects on sustainable livelihoods, living conditions, and social development among small business owners and individuals operating within the informal sector.